TINJAUAN YURIDIS PEMBEBASAN LAHAN UNTUK KEPENTINGAN UMUM DALAM PRESPEKTIF HAK MILIK DAN PENGGANTIAN KERUGIAN MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Taibu, Rachmat; Saputra, Fikhram Surya (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
The problems formulated in this research are: What are the legal provisions concerning land acquisition for public interest from the perspective of ownership rights according to legislation; and what are the common obstacles in the process of land acquisition for public interest as well as the solutions and settlements? This research uses a normative juridical method with a descriptive qualitative approach. Data were obtained through a literature review of laws and regulations, legal documents, and scientific literature, and were complemented by field data through observation and documentation in the Baubau City area. The research results indicate that land acquisition for public interest does not fully guarantee the protection of ownership rights. In many cases, the compensation given does not align with the social and economic value of the land acquired, and there is minimal community involvement in the deliberation process. Furthermore, gaps in regulatory implementation hinder the achievement of substantive justice. Therefore, synchronization is needed between normative regulations and their implementation in the field, as well as a transparent, accountable, and participatory land acquisition mechanism. This research recommends that the government and related institutions prioritize legal principles that ensure fairness and equality in every land acquisition process. There is a need for legal education for the community regarding their rights, as well as the importance of strengthening legal instruments that can ensure certainty and protection of ownership rights in every form of land procurement for public interest. It is hoped that this research can contribute valuable thoughts to the development of agrarian law in Indonesia.